2021
DOI: 10.3390/jcm10173872
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the COVID-19 Pandemic on the Stress Levels and Occurrence of Stomatoghnatic System Disorders (SSDs) among Physiotherapy Students in Poland

Abstract: Background: This study is a quantitative analysis examining the impact of the COVID-19 pandemic on the occurrence of stress and stomatognathic system disorders (SSDs) among students of physiotherapy. Objective: To assess stress severity, strategies of coping with stress and the presence of type D personality among physiotherapy students including those with symptoms of stomatognathic system disorders. Material and Methods: The research was conducted from October to December 2020 on a sample of 188 students of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 75 publications
3
9
0
1
Order By: Relevance
“…As other studies show, we found high levels of mental distress, especially elevated levels of anxiety and depression in more than half of our participants (62% and 61% respectively) [ 33 ]. Our results show some slight differences from international studies, with a higher rate of depression compared with other research and, when compared to a recent review reporting PTSD prevalence among HW during COVID-19 pandemic, lower post-traumatic symptomatology [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 77%
“…As other studies show, we found high levels of mental distress, especially elevated levels of anxiety and depression in more than half of our participants (62% and 61% respectively) [ 33 ]. Our results show some slight differences from international studies, with a higher rate of depression compared with other research and, when compared to a recent review reporting PTSD prevalence among HW during COVID-19 pandemic, lower post-traumatic symptomatology [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 77%
“…The respondents with significantly reduced mental well-being use maladaptive coping strategies, such as denial of problems, emotional discharge, taking in psychopharmaceuticals, doing nothing and self-blaming. Similar results were obtained in physiotherapy students, where the main strategies for coping with stress were positive re-evaluation, discharging, self-blaming and taking psychopharmaceuticals [ 51 ]. Another report also indicated that younger adults (like students) were under greater stress during the pandemic.…”
Section: Discussionsupporting
confidence: 72%
“…That, in turn, had a negative impact on the mental and physical health of students and university graduates. The accompanying stressors could have had influenced the development of increased masticatory muscles tension and numerous parafunctions, and thus the formation of stomatognathic system dysfunctions [ 1 , 2 , 3 , 4 , 5 ]. The relationship between increased stress and disorders of the stomatognathic system and quality of life has been widely described in the literature [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%